The Effect of MSME Credit, Non-Performing Loans, BI Interest Rates, and Capital Adequacy Ratio on Profitability (A Case Study of PT Bank Rakyat Indonesia Tbk) - B. Andreas Mada; M. Ghaniy Arrasyid (Journal of Business, Finance, and Banking, 2026)
This study aims to determine the effect of People’s Business Credit (KUR) Distribution, Non Performing Loan (NPL), Bank Indonesia Rate Level and Capital Adequacy Ratio (CAR) on profitability at PT Bank Rakyat Indonesia (Persero) Tbk for the period 2016-2023. The population in this study were all financial reports published by PT Bank Rakyat Indonesia (Persero) Tbk for the period 2016-2023. The sampling technique used was purposive sampling with the criteria for presenting data on people’s business credit distribution, Non Performing Loan (NPL), Bank Indonesia Rate Level and Capital Adequacy Ratio (CAR) and profitability at PT Bank Rakyat Indonesia (Persero) Tbk for the period 2016-2023. The data analysis of this study used SPSS. The results of the study showed that the People's Business Credit (KUR) Distribution variable partially had a positive and significant effect on the profitability of PT Bank Rakyat Indonesia with a significant value of 0.044. The Non Performing Loan (NPL) variable partially has a negative and significant effect on the profitability of PT Bank Rakyat Indonesia with a significant value of 0.017. The Bank Indonesia Interest Rate variable partially has a positive and significant effect on the profitability of PT Bank Rakyat Indonesia with a significant value of 0.031. While the Capital Adequacy Ratio (CAR) variable partially has a positive and insignificant effect on the profitability of PT Bank Rakyat Indonesia with a significant value of 0.083. This study shows that 58% of the profitability of PT Bank Rakyat Indonesia is influenced by the Distribution of People's Business Credit, Non Performing Loan (NPL), Bank Indonesia Interest Rate and Capital Adequacy Ratio (CAR) together.